2021
DOI: 10.1093/rheumatology/keab249
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies and safety of rechallenge in the setting of immune checkpoint inhibitors-related myositis: a national multicentre study

Abstract: Objectives The occurrence of immune-related myositis (irM) is increasing, yet there are no therapeutic guidelines. We sought to analyze the current therapeutic strategies of irM and evaluate the outcomes of immune checkpoint inhibitors (ICI) rechallenge. Methods We conducted a nationwide retrospective study between April 2018 and March 2020 including irM without myocardial involvement. Depending on the presence of cutaneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Studies having specifically assessed the safety of ICI retreatment after ICI discontinuation for irAEs remain scarce and heterogenous. Most are based on small samples of patients [ 18 , 19 , 20 ] or focused only on the recurrence rate of the same irAE after an ICI rechallenge [ 21 ]. Moreover, patients with grade ≥3 irAEs have been excluded from many of these studies [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies having specifically assessed the safety of ICI retreatment after ICI discontinuation for irAEs remain scarce and heterogenous. Most are based on small samples of patients [ 18 , 19 , 20 ] or focused only on the recurrence rate of the same irAE after an ICI rechallenge [ 21 ]. Moreover, patients with grade ≥3 irAEs have been excluded from many of these studies [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four of 5 patients did not have a flare, whereas one had recurrent MG and myositis with respiratory failure and recovered 15 . In a more recent case series, 9 patients (2 severe) with isolated ICI myositis were rechallenged with ICI within 4 months of the ICI myositis occurrence, and none of these patients experienced relapse of myositis at median follow-up of 457 days 36 . Interestingly, 6 of 9 patients were given steroids preemptively for approximately 3 months (10–50 mg prednisone daily).…”
Section: Rechallengementioning
confidence: 93%
“…Necrosis can range from multifocal clusters to diffuse confluent areas with myophagocytosis and regenerating fibers 9,10,14,23 . Atrophic muscle fibers are usually scattered and intermixed; however, there are also reports of perifascicular predominant distribution 10,36 . Strong MHC-1 staining is reported especially in degenerating muscle fibers 14,23 .…”
Section: Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Weill et al reported that none of the 9 patients in their national multicentre study that were rechallenged with ICIs had a relapse of myositis, though one patient developed immune-related colitis. Of note, none of the patients in the study had myocardial involvement, and some patients were excluded from rechallenge due to severity and safety reasons (61). Hence, ICI rechallenge appears to be a potentially feasible option after deliberation between the muscle and cancer specialist and the patient with careful consideration of the clinical presentation and severity of disease.…”
Section: Managementmentioning
confidence: 99%